Glacier maxima in Baffin Bay during the Medieval Warm Period coeval with Norse settlement ... - Young, Nicolas E.; Schweinsberg, Avriel D.; Briner, Jason P.; Schaefer, Joerg M. (Columbia University, 2015)
The climatic mechanisms driving the shift from the Medieval Warm Period (MWP) to the Little Ice Age (LIA) in the North Atlantic region are debated. We use cosmogenic beryllium-10 dating to develop a moraine chronology with century-scale resolution over the last millennium and show that alpine glaciers in Baffin Island and western Greenland were at or near their maximum LIA configurations during the proposed general timing of the MWP. Complimentary paleoclimate proxy data suggest that the western North Atlantic region remained cool, whereas the eastern North Atlantic region was comparatively warmer during the MWP—a dipole pattern compatible with a persistent positive phase of the North Atlantic Oscillation. These results demonstrate that over the last millennium, glaciers approached their eventual LIA maxima before what is considered the classic LIA in the Northern Hemisphere. Furthermore, a relatively cool western North Atlantic region during the MWP has implications for understanding Norse migration ...